CUSTOM HIRING VERSUS OWNERSHIP OF AGRICULTURAL MACHINERY SERVICES IN RICE PRODUCTION FARMS IN ALNAJAF AL-ASHRAF PROVINCE - KADHIM, Z. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Investments in ownership of agricultural machinery services and access to them, especially for small-scale farmers, may not be the minimum cost option in comparison with hiring these required services through oral or written agricultural hire contracts. The main objective of this research is to test whether the custom hiring status of agricultural machinery services is better for selected sample in comparison with the other potential alternatives. The theoretical framework based on the financial approach of engineering costs analysis of agricultural machineries services, to calculate discounted cash flows. The data were collected by using cross- section data in rice production farms in Alnajaf Al-ashraf province during 2015 farming season. The results indicated that the total costs of the used machineries are lower purchasing price, fixed costs and requires more powered skills than new machineries. Results also pointed out that the values of net present criterion had negative sign and less than zero at 5%, 7% and 10% discount rates because of the costs of financing exceed total revenues earned from agricultural machineries in addition to the results showed that the investments on all new and used agricultural machinery in the study area are unprofitable based on profitability ratio criteria. The custom hire should be encouraged for enhancing the use of agricultural machinery services in the province due to it is highly profitable from the individual investor viewpoint.